Case Report: Possible C3 nephritic factor–driven complement-mediated severe hemolytic anemia and acute kidney injury in a child with Bordetella parapertussis infection - Thorsen, Steffen Ullitz; Hansen, Anne Todsen; Hartling, Hans Jakob; Marquart, Hanne Vibeke; Borgwardt, Line; Laustsen, Mira Marie; Skattum, Lillemor; Nielsen, Alex Christian Yde; Sehested, Line Thousig; Nørgaard, Hanne; Dziegiel, Morten Hanefeld; Schmidt, Ida Maria (Frontiers in Immunology, 2026)
Overactivation of the complement system can cause life-threatening intravascular hemolysis, acute kidney injury (AKI), and multi-organ failure. Expanding the spectrum of rarer triggers of complement dysregulation that may cause severe hemolysis is essential for timely diagnosis and treatment. We report the case of a three-year-old boy admitted with macroscopic hematuria and jaundice. The patient tested positive for Bordetella parapertussis. Atypical hemolytic uremic syndrome (aHUS) was initially suspected due to decreasing hemoglobin, platelet count, and worsening of AKI, and empirical treatment with eculizumab (ECZ) was initiated. No red blood cell (RBC) autoantibodies were detected by standard serology methods or extended flow cytometry including antibody fixation at both room temperature and 4°C, no underlying hematological disorder was found, and genetic screening revealed no pathogenic variants associated with aHUS. However, the patient was strongly positive for C3 nephritic factor (C3NeF), an autoantibody stabilizing the C3 convertase (C3bBb) of the alternative complement pathway. C3NeF is typically linked to C3 glomerulopathy, but in this case appears to have triggered severe complement overdrive and extra- and intravascular hemolysis (bystander hemolysis) during an infection (two-hit immunopathology). Concomitantly, B. parapertussis is known to bind complement factor H, a key regulator of the alternative pathway, creating a “perfect storm” of dysregulation. Following infection control and complement blockade with ECZ, C3d deposition on RBCs declined, renal function recovered, and no clinical relapse has been observed 2 years and 6 months after discharge. To our knowledge, this is the first reported case of a possible C3NeF-driven complement-mediated severe hemolysis with associated AKI due to free hemoglobin toxicity during a severe infection.